2014
DOI: 10.5551/jat.18085
|View full text |Cite
|
Sign up to set email alerts
|

Dolichocarotids: Echo-Color Doppler Evaluation and Clinical Role

Abstract: Aims: Dolichocarotids (DCs) represent a rare (2-6%) carotid imaging finding in the general population that may be free of clinical significance or be associated with cerebrovascular events. Their detection is traditionally assigned to carotid echo-color Doppler (ECD) and selective angiography (the standard method). The primary aim of this study was to estimate the sensitivity, specificity and accuracy of ECD in detecting DCs. Moreover, we monitored the DC curvature angle and the incidence of TIA, ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The clinical role of dolichocarotids is currently unclear, and studies have denied an association between these carotid abnormalities and cerebrovascular events. One study found kinking to be more frequently associated with cardiovascular death than tortuosity, 35 and another study showed that dolichocarotids are associated with dilated cardiomyopathy. 36 However, only a small proportion of patients (2% to 6%) have dolichocarotids and, in our study, we did not consider dolichocarotids as a confounding factor associated with cardiovascular-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical role of dolichocarotids is currently unclear, and studies have denied an association between these carotid abnormalities and cerebrovascular events. One study found kinking to be more frequently associated with cardiovascular death than tortuosity, 35 and another study showed that dolichocarotids are associated with dilated cardiomyopathy. 36 However, only a small proportion of patients (2% to 6%) have dolichocarotids and, in our study, we did not consider dolichocarotids as a confounding factor associated with cardiovascular-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions relevant to development of atherosclerosis (e.g., chronic obstructive pulmonary disease, autoimmune disorders), were not rigorously assessed. Aspects of vessel morphology linked to CVD risk (i.e., dolichocarotids 30, 31 ) were not systematically assessed and should be considered in future work. Further, IMT was assessed once at visit 12; thus trajectories of IMT could not be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to restrict inclusion criteria to a relatively homogeneous population of asymmetric IC stenosis patients with no cervical stenosis >70%, and we perform multivariate analysis of the major stroke risk factors only (Supplementary Material). We did not control for dolichoectasia, although patients with dolichoectasia and related cerebrovascular morphological abnormalities of cervical vessels may have increased stroke risk 17, 18 . Unfortunately, our patients do not routinely undergo carotid echo-color Doppler and only a subset of our patients had cerebral angiography; larger studies that assess the relationship of CVR with other stroke risk factors may benefit by incorporating separate measurements of dolichoectasia.…”
Section: Discussionmentioning
confidence: 99%